Pengembangan sistem jaminan halal produk minuman herbal instan di industri kecil menengah (ikm) “dia” - Teti Estiasih; Kgs Ahmadi; Harijono Harijono (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Indonesian law obliges that all marketed, distributed, and trade products in the territory of Indonesia should have comply halal requiremnets. Small and Medium Enterprise (SME) DIA produces instant herbal drink products with the largest consumer is being Muslim. In accordance with the law, thatall products are required to halal certified and have a halal logo on the label, the SME DIA also prepares for halal certification. To certify halal, a halal assurance system must be implemented. Development of halal assurance system is required for small and medium industries in order to halal certification. Development of the halal assurance system is based on the HAS 23000 guide from LPPOM MUI. In fulfillment of HAS 23000, SME DIA has implemented 11 clausuls that are halal policy, halal management team, materials, products, production facilities, training and education, written standardoperating procedures, traceability, uncomplied halal product handling, internal audit, and management review. HCCCP analysis shows that no halal critical points in producing instant herbal drinks at SME DIA.